The game inventor's guidebook : how to invent and sell board games, card games, role-playing games, and everything in between - Tinsman, Brian (Garden City, NY : Morgan James Pub., 2008)
Insider's views highlight Brian Hersch, Richard Tait and Whit Alexander, George Parker, Mike Fitzgerald, Alan Moon, Jordan Wissman, Paul Randles, and various publishers.
-- How they did it. Trivial pursuit /Chris Haney and Scott Abbott -- Magic : the gathering /Richard Garfield -- Dungeons and dragons /Gary Gygax and Dave Arneson -- Pokemon trading card game -- Tsunekaz Ishihara, Kouichi Ooyama, Takumi Akabane -- Interview with an inventor /Reiner Knizie -- Interview with a publisher /Mike Gray -- How the industry works. What's in it for you -- How new games happen -- Anatomy of a publisher -- Markets for games -- Games and companies you should know. Mass market games you should know -- Mass market companies you should know -- Hobby games you should know -- Hobby game companies you should know -- American specialty games and companies you should knwo -- European games, companies, and an award you should know -- Self-publishing -- Selling a game step by step. How to invent a game -- Game design -- Game development -- Targeting publishers -- Before you submit -- Eight submission strategies -- Contacting publishers -- Protecting your property -- What to do if they say don't say yes -- What to do if they do say yes! -- Game industry's dirty little secret -- Details and resources -- Other resources.
"Habitat for Humanity" -- t.p. verso ; cover, pages4.
Includes bibliographical references.
Keywords: Games -- Marketing; Games -- Design and construction -- Case studies; Board game industry -- United States -- Handbooks, manuals, etc; Playing card industry -- Handbooks, manuals, etc. -- United States